Profitabilitas, Leverage, dan Slack Resources terhadap Corporate Social Responsibility (CSR) Perusahaan Energi Terdaftar di Bursa Efek Indonesia periode 2019–2023 - Annisa Naura Fayza; HN Hartikayanti (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the effect of profitability, leverage, and slack resources on Corporate Social Responsibility Disclosure (CSRD) in energy sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This study uses a quantitative approach with a causality design and identification of associative problems. The sampling technique uses purposive sampling based on the criteria of companies that have consistently published sustainability reports for 5 years. The analysis technique used is multiple linear regression with classical assumption tests including normality, multicollinearity, and autocorrelation tests. The results show that simultaneously the variables of profitability, leverage, and slack resources influence Corporate Social Responsibility Disclosure (CSRD), but partially only slack resources have a significant effect on the level of CSRD disclosure, while the variables of profitability and leverage do not show a significant effect on CSRD disclosure in energy sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. These findings confirm that the flexibility of a company's internal liquidity plays an important role in encouraging social disclosure and sustainability reporting.